The discursive construction of ideological stability: deconstructive analysis of sustainability discourse in the ESG reports of global oil corporations - Tutar, Hasan; Gasimov, Ragif (Transformations In Business & Economics, 2026)
This study aims to understand how the sustainability discourse reproduces ideological stability in the ESG reports published by global oil companies between 2014 and 2024. The study also attempts to reveal how sustainability has transformed into a hegemonic ethical form as a discursive tool. The study assumes that ESG reports focus on the legitimization function inherent in neoliberal norms, rather than the companies’ claims of sensitivity. The study employed Critical Discourse Analysis (Fairclough) and Deconstructive analysis (Derrida), utilizing qualitative research methods. The annual ESG reports of ExxonMobil, BP, and Shell were selected as samples, and these documents were subjected to critical discourse analysis. The analysis focused on coherence, transformation, and ruptures in the discourses, evaluating the texts within the framework of continuous deferral of meaning and resolution of binary oppositions. The findings show that the sustainability discourse has been institutionalized over time, being associated with ethics (greenwashing), and has functioned as a tool of ideological stability beyond environmental responsibility. ESG discourse is evaluated as a hegemonic tool reconstructed in the context of environmental or social responsibility to maintain corporate legitimacy.